2016
DOI: 10.1080/21645515.2016.1191718
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic variability: Obstacles on the road to vaccines against traditionally difficult targets

Abstract: Despite the impressive impact of vaccines on public health, the success of vaccines targeting many important pathogens and cancers has to date been limited. The burden of infectious diseases today is mainly caused by antigenically variable pathogens (AVPs), which escape immune responses induced by prior infection or vaccination through changes in molecular structures recognized by antibodies or T cells. Extensive genetic and antigenic variability is the major obstacle for the development of new or improved vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 107 publications
(142 reference statements)
0
32
0
Order By: Relevance
“…25 According to the cancer immune surveillance theory, opposing forces act to maintain the equilibrium between the elimination of tumor cells and immune escape, mediated by repeated cycles of immune pressure and the selection of cancer cells carrying certain mutation(s). 13,30 Extensive data are underpinning the striking similarities between cancer and antigenically variable pathogens, such as viruses, in terms of induced immune responses, 23 which in turn, allow us to conclude that the successful vaccine against antigenically variable pathogens should share critical features of the vaccine immunogen intended to treat cancer. Indeed, a recent study applying a neoantigen fitness model to predict the survival of patients treated with immune checkpoint inhibitor therapy revealed broad similarities between the evolution of tumors and rapidly evolving pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 According to the cancer immune surveillance theory, opposing forces act to maintain the equilibrium between the elimination of tumor cells and immune escape, mediated by repeated cycles of immune pressure and the selection of cancer cells carrying certain mutation(s). 13,30 Extensive data are underpinning the striking similarities between cancer and antigenically variable pathogens, such as viruses, in terms of induced immune responses, 23 which in turn, allow us to conclude that the successful vaccine against antigenically variable pathogens should share critical features of the vaccine immunogen intended to treat cancer. Indeed, a recent study applying a neoantigen fitness model to predict the survival of patients treated with immune checkpoint inhibitor therapy revealed broad similarities between the evolution of tumors and rapidly evolving pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…22 In recent years, we have developed a new class of vaccine immunogens, coined as variable epitope libraries (VELs), based on complex combinatorial libraries carrying from thousands to millions of mutated versions of Tcell epitopes, in order to address antigenic variability, which is observed as a common critical issue in the field of vaccines against many pathogens and cancer. 23 The feasibility of a VEL-based vaccine platform has been demonstrated in our previous studies where we have shown that an HIV-1 epitope-based VEL induced broadly neutralizing sera in mice that was capable of neutralizing >50% of Tier 2 viruses tested. 24 Furthermore, a VEL vaccine derived from a survivin (SVN) epitope has been successfully tested in the mouse 4T1 breast tumor model leading to significant tumor growth inhibition upon a single immunization during therapeutic treatment.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 91%
“…Allergencity is an important factor in vaccine design as allergic reaction could be fatal to the patients and hence we tested the allergencity of our proposed vaccine using allertop software which confirm the non allergencity of the vaccine. (62) Furthermore the antigenicity is a significant factor to tack into account when choosing a target for vaccine design, (63) therefore we tested the antigenicity of mhc1 and mhc2 peptide using vaxiJen software which shows 4 peptides to be antigenic in mhc1(YLYRYGYTR, WRFDVKAQM, LIADKWPAL, MYPMYRFTE) and one peptide to be antigenic in mhc2 (RRLWRFDVKAQMVD). (Table 7)…”
Section: Discussionmentioning
confidence: 99%
“…However, newly emerging and reemerging infectious diseases (ERID), infectious agents with complex lifecycle and antigenic variability and the need for personalized vaccination present additional challenges in vaccine development. 2,3 For many pathogens (especially the emerging and those with antigenic variability), their genomes are known but their immune correlates of protection remain unclear. 1,4 Some of these reasons are why vaccine development for ERID and multi-lifecycle pathogenic diseases is a tall order.…”
Section: Introductionmentioning
confidence: 99%